2022
DOI: 10.3390/cancers14215272
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies and a Retrospective Cohort Study: The Interaction between PPAR Agonists and Immunomodulatory Agents in Multiple Myeloma

Abstract: Our previous study demonstrated that peroxisome proliferator-activated receptor (PPAR) agonists downregulated cereblon (CRBN) expression and reduced the anti-myeloma activity of lenalidomide in vitro and in vivo. We aimed to determine whether DNA methylation and protein degradation contribute to the effects of PPAR agonists. CRBN promoter methylation status was detected using methylation-specific polymerase chain reaction. The CRBN protein degradation rate was measured using a cycloheximide chase assay. Metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…We found that PPAR agonists affected the CRBN promoter CpG island methylation pattern and caused hypermethylation in the CRBN promoter region. Moreover, CRBN was rapidly degraded upon exposure to PPAR agonists [43]. Although several mechanisms for this drug-drug interaction have been suggested, none has been proven.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that PPAR agonists affected the CRBN promoter CpG island methylation pattern and caused hypermethylation in the CRBN promoter region. Moreover, CRBN was rapidly degraded upon exposure to PPAR agonists [43]. Although several mechanisms for this drug-drug interaction have been suggested, none has been proven.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation is one of the epigenetic events that plays important roles in transcriptional repression, genomic imprinting, and genomic stability [41,42]. Our previous study showed that PPAR agonists induced DNA methylation in the CpG islands of the CRBN promoter region [43]. Here, to further analyze the mechanism underlying the enhanced effects of RXR agonists on CRBN transcription, we performed methylation-specific PCR (MSP) to evaluate the methylation or demethylation status of the CpG island in the CRBN promoter region.…”
Section: Rxr Agonists Facilitated Dna Demethylation In the Cpg Island...mentioning
confidence: 99%
“…Whereas two old studies highlighted its ability to decrease myeloma cell growth through the down-regulation of NFκB activity [ 29 , 30 ], two very recent papers demonstrated PPAR β/δ upregulation in the BM CD138+ plasma cells and BM CD138− microenvironment cells in patients with newly diagnosed MM compared with those in normal BM controls, and a higher PPAR β/δ expression was associated with worse progression-free survival (PFS) and overall survival (OS) [ 31 , 32 ]. Moreover, Wu et al investigated the drug–drug interactions between immunomodulatory agents (IMiDs) and PPAR agonists in patients with MM, demonstrating opposite metabolic effects of these molecules in MM cells [ 32 ]. Through a retrospective study, they assessed that the coadministration of a PPAR agonist with IMiDs was associated with worse PFS and OS in MM patients with co-existing type II diabetes and/or dyslipidemia [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Wu et al investigated the drug–drug interactions between immunomodulatory agents (IMiDs) and PPAR agonists in patients with MM, demonstrating opposite metabolic effects of these molecules in MM cells [ 32 ]. Through a retrospective study, they assessed that the coadministration of a PPAR agonist with IMiDs was associated with worse PFS and OS in MM patients with co-existing type II diabetes and/or dyslipidemia [ 32 ]. However, neither study investigated the link between PPAR β/δ and angiogenesis in MM.…”
Section: Introductionmentioning
confidence: 99%
“…8 Recently, inhibition of PIM kinases has emerged as a hot spot in drug development, and has been widely used to reduce glycolysis, increase T cell persistence, and control tumor processes. 9 10 11…”
Section: Introductionmentioning
confidence: 99%